Perilaku Seksual Lesbian, Gay, Biseksual,Transgender, dan Risikonya terhadap Infeksi Menular Seksual - Puspitasari, Monika; Susetiati, Devi Artami; Siswati, Agnes Sri (Cermin Dunia Kedokteran, 2023)
Lesbian, gay, bisexual, transgender (LGBT) face many gaps in sexual health aspects, including an increased risk of human immunodeficiency virus (HIV infection), sexually transmitted infections (STIs), and pregnancy. LGBT often experience social stigmatization, isolation, and rejection, even from their respective parents. Risk of STIs is related to sexual orientation, sexual anatomy, and sexual behaviour. LGBTs sexual activity may vary and with multiple partners, who are vulnerable to transmission of STIs and HIV infection. Health care providers are responsible for an open discussion regarding sexual health issues; including sexual orientation, sexual behavior, and gender identity.